2011
DOI: 10.1111/j.1468-2494.2011.00693.x
|View full text |Cite
|
Sign up to set email alerts
|

A combined approach in characterization of an effective w/o hand cream: the influence of emollient on textural, sensorial and in vivo skin performance

Abstract: To formulate a consumer-acceptable cosmetic product, numerous demands have to be fulfilled, and as the most important, efficacy (both real and perceived), adequate aesthetic (visual perception) and all sensorial characteristics have to be achieved. In this study, four model water-in-oil creams intended for hand care, varying in one emollient component, were submitted to rheological, sensory and textural characterization, and their efficacy was evaluated in in vivo study on human volunteers. Our results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
102
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 24 publications
(31 reference statements)
5
102
0
6
Order By: Relevance
“…Comparison of the rheograms of O/W emulsions containing different emulsifier systems and different oils but the same aqueous phase revealed that the shape of the obtained flow curves and hysteresis loops was similar (data not shown). Other authors [18] reported that emulsion flow behavior mostly depends on the rheological properties of continual phase rather than on the microstructure of the emulsion system (disperse phase). In our study, no relationship was observed between emulsion thixotropic behavior and emulsion composition.…”
Section: Physicochemical Properties Of Emulsions A-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the rheograms of O/W emulsions containing different emulsifier systems and different oils but the same aqueous phase revealed that the shape of the obtained flow curves and hysteresis loops was similar (data not shown). Other authors [18] reported that emulsion flow behavior mostly depends on the rheological properties of continual phase rather than on the microstructure of the emulsion system (disperse phase). In our study, no relationship was observed between emulsion thixotropic behavior and emulsion composition.…”
Section: Physicochemical Properties Of Emulsions A-cmentioning
confidence: 99%
“…Therefore, many studies have been focused on sensory evaluations of cosmetics to fulfill consumers' needs by formulating products that offer both adequate efficacy and aesthetic characteristics [15][16][17]. Recently, Lukic et al [18], evaluating the effects of emollients on textural, sensorial and in vivo skin performance of cosmetic O/W emulsions, reported that the oily phase composition affected all investigated characteristics, evidencing that the replacement of only one oil could make a significant change.…”
Section: Introductionmentioning
confidence: 99%
“…No wonder that sensory analysis dominates in the process of their production (see Lukic et al [2]). This methodology of sensory evaluation of cosmetic products follows three principal points: suitable choice of evaluated variables, suitable choice of the corresponding absolute or universal scales, and suitable choice of a professional panel (expensive).…”
Section: Introductionmentioning
confidence: 99%
“…Danov [8] proposed an analytical expression for the viscosity of dilute emulsions in the presence of emulsifiers as already mentioned above. Lukic et al [2] studied four water-in-oil creams differing in only one emollient component. The samples were submitted to rheological, sensory and textural characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory evaluation is used to measure, analyze and interpret the characteristics of products according to the perception of the four senses (sight, smell, taste and touch). Although initially this analysis was used for food and beverages, sensory evaluation is widely applicable in pharmaceuticals, cosmetics and toiletries, such as toothpaste, shampoo, etc [5][6][7][8][9] . The sensory evaluation of a cosmetic product is of paramount importance, as it affects the acceptance of the product by the consumer and consequently its potential for trade 6 .…”
mentioning
confidence: 99%